Freedom on the Border : An Oral History of the Civil Rights Movement in Kentucky - K'Meyer, Tracy Elaine; Fosl, Catherine (Kentucky remembered., 2009)
In this book, Fosl and K'Meyer "gather the voices of more than one hundred courageous crusaders for civil rights, many of whom have never before spoken publicly about their experiences. These activists hail from all over Kentucky, offering a wide representation of the state's geography and culture while explaining the civil rights movement in their respective communities and in their own words."--Book jacket.